2014
DOI: 10.18052/www.scipress.com/ilns.17.152
|View full text |Cite
|
Sign up to set email alerts
|

Induced Physical Mutagenesis and its Effect in Cytological Behavior of Ashwagandha (<i>Withania somnifera</i> (L.) Dunal)

Abstract: The mitotic effect of physical mutagen gamma rays was observed in the root tip cells of Ashwagandha. The Chromosome analysis has been showed as an important tool for establish variability of the plant seed by use of physical mutagen gamma rays. The gamma rays have of low wavelength and high penetrable power. The plant has tremendous medicinal values and it is known from ancient times. The dry and well matured seeds of ashwagandha were irradiated with different doses of gamma rays viz., 5,10,15,20,25,30,35, 40,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
1
2
1
1
Order By: Relevance
“…The study revealed that pollen fertility decreased with an increase in dose/concentration of the mutagens (Bashir et al, 2016). Delayed in first flowering in ashwagandha was reported by the irradiated the seeds with different dose of gamma rays (Bharathi et al, 2013). Our result was also same as we also found delayed in flowering in gamma rays irradiated plants.…”
Section: Effect Of Irradiation On Flowering and Yields Attributing Chsupporting
confidence: 91%
“…The study revealed that pollen fertility decreased with an increase in dose/concentration of the mutagens (Bashir et al, 2016). Delayed in first flowering in ashwagandha was reported by the irradiated the seeds with different dose of gamma rays (Bharathi et al, 2013). Our result was also same as we also found delayed in flowering in gamma rays irradiated plants.…”
Section: Effect Of Irradiation On Flowering and Yields Attributing Chsupporting
confidence: 91%
“…Furthermore, the range of gamma rays doses tested did not significantly affect the germination percentage of R. lineatus and R. chrysophyllus seeds. It is slightly different with certain studies performed on seeds of several species such as Withania samnifera (Bharathi et al, 2013), Citrus jambhiri (Sharma et al, 2013), Cajanus cajan (Ariraman et al, 2014) that a gradual decrease in seed germination from lower doses to higher doses of gamma rays were observed. In the other hand, Giovani et al (2015) reported that the effect of gamma rays at 50, 100 and 200 Gy were able to increase seed germination of Rosa hybrida.…”
Section: Mutation Breeding On Rubus Lineatuscontrasting
confidence: 59%
“…Then the spindle fiber pulled the chromosome towards the poles thus bridges were broken into fragments. This fragment has to move either towards the poles or formed the laggards [22]- [23]. As the consequence, omission of the arrival of chromatids at the poles caused of the event of fragments at metaphase [24].…”
Section: B Determination Of Chromosomal Behaviormentioning
confidence: 99%